Bifunctional Electrocatalyst with 0D/2D Heterostructure for Highly Efficient Hydrogen and Oxygen Generation. Issue 18 (8th September 2020) - Yu, Xueping; Yang, Chan; Zhang, Shan; Xing, Yonglei; Liu, Chuntai; Peng, Juan; Yan, Qingyu
Abstract: A novel MoS2 quantum dots/CoSe2 nanosheet (MoS2 QDs/CoSe2 ) hybrid with 0D/2D heterostructure has been developed. The CoSe2 nanosheets (NSs) enable an excellent oxygen evolution reaction (OER) activity with increasing vacancy configuration on one hand, while the MoS2 QDs serve as an eminent hydrogen evolution reaction (HER) catalyst on the other. By integrating MoS2 QDs and CoSe2 NSs, the hybrid exhibits excellent electrocatalytic performances in HER and OER. The unique 0D/2D hetero‐interface increases the exposed active sites and facilitates electron transfer, thereby boosting the electrocatalytic activity. Relatively low overpotentials of 82 mV and 280 mV are required to drive the current density of 10 mA/cm 2 for HER and OER, with corresponding Tafel slopes of 69 and 75 mV/dec, respectively. As such, this work provides an efficient yet simple approach to construct bifunctional electrocatalysts with enhanced activity and stability. Abstract : A MoS2 quantum dots/CoSe2 nanosheet (MoS2 QDs/CoSe2 ) hybrid with 0D/2D hetero‐structure is developed. The hybrid exhibits prominent electrocatalytic activity and satisfactory durability towards both HER and OER. Relatively Low overpotentials of 82 mV and 280 mV are required to drive the current density of 10 mA/cm 2 for HER and OER, with corresponding Tafel slopes of 69 and 75 mV/dec, respectively. Furthermore, this work provides an efficient yet simple method to construct bifunctional electrocatalysts with enhanced activity and stability.